(untitled) (Research, Society and Development, 2021)
Suicide is a serious public health problem worldwide. Safe Communication is an important resource for preventing suicide through awareness, a welcoming approach, seeking help, disseminating preventive content and reducing content or interactions that increase the risk of suicide among vulnerable individuals. The aim of this study was to analyze barriers and facilitators of safe communication about suicide in discursive productions about experiences and messages of support. It is a qualitative study, carried out in a virtual environment and submitted to Thematic Analysis. Among the “Facilitators” were identified: “The incentive to seek professional help”, “The propensity to offer help” and “The belief in the possibility of overcoming”. Among the "Barriers" related to safe communication about suicide, three categories were built: "Refusal of Help and Difficulty in offering help", "Stigma and Guilt" and "Concern about Unpreparedness". Between “Ambivalent Possibilities”, we found “Religiosity” and “Personal experience and advice”. The possibility of identifying facilitators and barriers for safe communication about suicide can be fundamental for the development of prevention and health promotion strategies, empowering facilitators and eliminating or reducing possible barriers.